Gold‐Catalyzed Cycloisomerizations of Functionalyzed Cyclopropyl Alkynes: the Cases of Carboxamides and Alcohols. Issue 17 (6th July 2017) - Fernández‐García, Jesús M.; Garro, Hugo A.; Fernández‐García, Laura; García‐García, Patricia; Fernández‐Rodríguez, Manuel A.; Merino, Isabel; Aguilar, Enrique
Abstract: Push‐pull alkynylcyclopropane derivatives are claimed as suitable and active substrates for gold‐catalyzed transformations. Thus, 2(3 H )‐azepinones can be readily prepared from alkynylcyclopropanecarboxamides through a nucleophilic addition/cyclopropane ring‐opening cascade process and, in this manuscript, the scope and the limitations of such reaction sequence are reported. The cascade reaction is general and occurs with complete regio‐ and quimioselection to form the seven‐membered heterocycles with the exception of primary alkyl‐substituted alkynylcyclopropanecarboxamides that render 4‐methoxy‐6‐oxo‐4‐enenitriles in moderate yields. Additionally, less activated alkynylcyclopropylmethanols undergo regioselective cycloisomerization at low temperature leading to oxabicyclo[4.1.0]heptanes. Notably, the cyclopropane ring opening of these adducts takes place under thermal conditions to form dihydropyranones. Abstract :